PENGARUH MOTIVASI TERHADAP KINERJA DOKTER DALAM PENGISIAN BERKAS REKAM MEDIS DI RSUD DELI SERDANG LUBUK PAKAM TAHUN 2017 - Rico Henando Sembiring (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2017)
A qualified medical record is needed to prepare for medical evaluation and audit on retrospective medical care and can be used for the evaluation of a hospital performance. Based on the preliminary survey conducted at RSU Deli Serdang, it was found that the percentage of incompleteness in filling out medical records was 45%, especially which was related to patients’ discharges. It is assumed that it is because of doctors’ non-optimal performance and the low motivation in filling out medical records. The objective of the research was to analyze the influence of motivation on doctors’ performance in filling out medical records at RSUD Deli Serdang, Lubuk Pakam. The research was an explanatory survey. The population was 80 doctors, and 45 of them were used as the samples. The data were gathered by conducting interviews and observation wit questionnaires and analyzed by using multiple regression analysis at α = 0.05. The result of the research showed that, statistically, the variable of intrinsic motivation (the achievement of performance, responsibility, and other people’s recognition) and extrinsic motivation (work relationship and work condition) had significant influence on doctors’ performance in filling out medical records at RSUD Deli Serdang, Lubuk Pakam. Intrinsic motivation of the achievement of performance had the most dominant influence on doctors’ performance in filling out medical records. It is recommended that the hospital management a) increase the role of Medical Committee, through the Ethics Committee, and continuously evaluate the implementation of completing medical records, b) increase socialization and sanction on the importance of completing and utilizing medical records regularly and sustainably, and c) give reward to doctors who have filled out medical records completely and punishment to those who have not filled them completely. Keywords: Motivation, Performance, Medical Record